(untitled) (BIRDEM Medical Journal, 2021)
Background: Carpal tunnel syndrome (CTS) is a chronic disabling condition of hands, occurring due to occupational and non-occupational risk factors, including high body mass index (BMI). This study was intended to find out the association of BMI with CTS. Methods: This was a cross-sectional analytical study was conducted in four teaching hospitals in Dhaka, Bangladesh from June 2017 to May 2018. Patients with electrophysiologically documented CTS were taken as cases and age matched healthy individuals without CTS were taken as controls. Following clinical and electrodiagnostic confirmation, data were collected from total 63 patients and 63 controls. Results: Mean BMI was 29.3±4.8 Kg/m2 in CTS group, which was higher than the control (24.1±3.3 Kg/m2). In CTS group, 56 (88.9%) had high BMI and 7 (11.1%) had normal BMI. On the other hand. 23 (36.9%) subjects in control group had high BMI and 40 (63.1%) had normal BMI. High BMI was significantly associated with carpal tunnel syndrome (p <0.01) but ncreasing BMI was not associated with severity of CTS (p 0.654). Conclusion: High BMI has a significant association with CTS but not with CTS severity. BIRDEM Med J 2021; 11(3): 179-185